Buoyancy Effects in Fluids - Chenvidyakarn, Torwong (International Journal of Building, Urban, Interior and Landscape Technology, 2011)
At first sight, it may appear rather odd to see the above title being reviewed in an architectural journal. After all, the name of the book seems to suggest its association with the world of science and mathematics rather than that of architecture. Further, it was first published nearly forty years ago, with the latest edition being almost a decade old, and so should be considered out-of-date. But there are good reasons for reviewing this seemingly irrelevant, out-of-date title. First of all, the book is—despite its name—in fact as relevant to architecture as it is to science and mathematics. Indeed, it may even be argued that, for graduate students and researchers in certain areas of architecture, this book is indispensible. Additionally, notwithstanding its age, the book is as relevant today as it was decades ago, even though its use— or indeed its existence—has not always been known by architecture students or academics. This review, then, hopes to reintroduce to the world of architecture a classic which it has long overlooked.